Physiological and morphological traits of tulip (Tulipa sp.) as affected by different concentrations of ethanol and methanol - Ramazannejad, Sajedeh; Sedaghathoor, Shahram (Ornamental Horticulture, 2021)
Tulip (Tulipa sp.) is of the highest economic importance and cultivated area among all bulbous ornamental species. The spray of alcohol is regarded as a proper strategy to improve plant yields in sustainable agriculture systems. This study aimed to investigate the effect of different rates of ethanol and methanol on the traits of the tulip in a factorial experiment based on a Randomized Complete Block Design with two factors including ethanol at four levels (0, 10, 20, and 30 vol%) and methanol at four levels (0, 10, 20, and 30 vol%). The estimated traits included anthocyanin, carotenoid, chlorophyll a and b, total chlorophyll, stem and leaf Brix index, leaf length and width, leaf area, total and bulb fresh and dry weight, leaf number, and flowering stalk length. Analysis of variance showed that the simple and interactive effects of different treatments were statistically significant on most estimated traits. The highest anthocyanin content (3.92 mg 100 g-1 DM), leaf length (25.83 cm), leaf area (258.6 cm2), and bulb fresh weight (25.81 g) were obtained from the plants treated with 30% ethanol, and the highest anthocyanin content (3.45 mg 100 g-1 DM) and leaf Brix index (10.15%) were related to 30% methanol. It can be concluded from the results that methanol and ethanol can be used as plant growth regulators.